Analysis of biochemcal parameters of adults with obesity submitted to the treatment of obesity by remote monitoring (Research, Society and Development, 2022)
Overweight and obesity are directly related to the development of Metabolic Syndrome and its isolated markers. To control some factors of the metabolic syndrome, biochemical indicators are used, such as: blood pressure, total cholesterol and fractions, glucose, insulin, and HOMA-IR. The Physical Education professional contributes to the development of actions that promote the adoption of healthy lifestyle habits as a means of preventing the incidence of obesity in Brazil. Therefore, the objective of the present work is to analyze the biochemical parameters of adults with obesity submitted to a multidisciplinary remote monitoring program for the treatment of obesity. This is a descriptive research with a quantitative approach, carried out with obese individuals in the city of Paranavaí. Inclusion criteria were individuals with obesity (BMI≥ 30Kg/m2), waist circumference ≥ 88 cm, and residents of the study municipality. The variables analyzed were blood glucose, insulin, us-CRP, total cholesterol, HDL, LDL, triglycerides, glycated hemoglobin. Participants received guidance 3 times a week, for 16 weeks, via Whatsapp, from professionals in the areas of Nursing, Physical Education, Psychology and Nutrition. The level of statistical significance adopted in all analyzes was p≤0.05 The intervention performed was effective in reducing biochemical markers, blood glucose (p-value: 0.014), insulin (p-value: 0.001), total cholesterol (p -value: 0.021) and HDL (p-value: 0.000). Thus, the remote treatment of obesity in adults performed in this study was effective in reducing the values ​​of biochemical markers glycemia, insulin, total cholesterol and HDL.